2006
DOI: 10.2214/ajr.04.1445
|View full text |Cite
|
Sign up to set email alerts
|

Renal Interlobar Artery Parameters with Duplex Doppler Sonography and Correlations with Age, Plasma Renin, and Aldosterone Levels in Healthy Children

Abstract: The RI in children up to 54 months old is higher than in adults. Therefore, the adult mean renal RI criterion of 0.70 should be applicable to children 54 months old and older. We showed that the age dependency of the RI was directly related to that of plasma renin and aldosterone levels in healthy children in whom Doppler parameters and blood analysis were evaluated synchronously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Other evidence regarding human renovascular diseases has further corroborated the association between chronic target organ damage and hyperaldosteronism. Interestingly, there have been several reports indicating that the resistive index is correlated to PAC [40,41]. A direct mineralocorticoid effect on the vessel wall could directly inhibit vasoconstriction in renal afferent arterioles, which is in sharp contrast to the vasoconstrictive response to increased renal perfusion pressure in primary aldosteronism [42].…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence regarding human renovascular diseases has further corroborated the association between chronic target organ damage and hyperaldosteronism. Interestingly, there have been several reports indicating that the resistive index is correlated to PAC [40,41]. A direct mineralocorticoid effect on the vessel wall could directly inhibit vasoconstriction in renal afferent arterioles, which is in sharp contrast to the vasoconstrictive response to increased renal perfusion pressure in primary aldosteronism [42].…”
Section: Discussionmentioning
confidence: 99%
“…Flow velocities were determined from signals that were stable for at least five pulse beats, and measurements represented the average of five complete waveforms. The resistance parameters, RI and PI were determined as follows: where PSV is peak systolic velocity, EDV is end‐diastolic velocity, and MV is mean velocity (time averaged velocity) (15).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that mean intrarenal RI is age-dependent, particularly in infants (Kuzmic et al, 2000;Murat et al, 2005;Sigirci et al, 2006;Vade et al, 1993;Wong et al, www.intechopen.com Hemodynamics -New Diagnostic and Therapeutic Approaches 6 1989). In children, the mean RI frequently exceeds 0.70 during the first year of life.…”
Section: Children and The Elderlymentioning
confidence: 99%
“…Maturation of renal blood flow rate is, to some extent at least, due to a decrease in renal vascular resistance (Murat et al, 2005). Sigirci et al (2006) suggested that intrarenal RI was higher for children up to 54 months old than for adults. Therefore, the adult mean intrarenal RI criterion of 0.70 should be applicable to children 54 months old and older.…”
Section: Children and The Elderlymentioning
confidence: 99%